Effect of withering temperature on water loss of fresh leaves and quality of white tea - LIN Qingxia; XIANG Lihui; WANG Lili; YANG Junguo; SONG Zhenshuo; CHEN Lin (浙江大学学报. 农业与生命科学版)
This study aimed to improve the withering process of the white tea manufacturing and to achieve the stability and controllability of white tea quality. Fresh leaves plucked from tea (Camellia sinensis) bushes of 15 cultivars were used to explore the effects of withering temperatures (30, 25, 20 ℃) on the dehydration rate, sensory quality and biochemical compositions of white tea. The contents of biochemical compositions were compared among the samples based on the two-dimensional point set distribution and principal component analysis. The results showed that the water loss rates of all tea shoots tended to decelerate gradually under the different withering temperatures, the higher the withering temperature, the faster the water loss rate. Dehydration rate equation was consistent with the hyperbolic function. Compared with the natural withering, the average withering time at 25℃ was significantly shortened by 13.6 h. The sensory evaluation suggested that the white tea prepared under the withering condition of 25℃ had the highest quality, which was equivalent to the quality under the natural withering. The analysis of biochemical composition found that there was no difference between withering at 25℃ and natural withering. In conclusion, the time of the white tea withering at 25℃ was greatly shorten and the quality of the prepared white tea was superior, which could further improve the production efficiency of the white tea, and provide effective references for the improvement of the white tea process.